Broader phenotypic traits and widespread brain hypometabolism in spinocerebellar ataxia 27. (19th March 2020) - Paucar, M.; Lundin, J.; Alshammari, T.; Bergendal, Å.; Lindefeldt, M.; Alshammari, M.; Solders, G.; Di Re, J.; Savitcheva, I.; Granberg, T.; Laezza, F.; Iwarsson, E.; et al.
Abstract: Objective: The goal of this study was to characterize a Swedish family with members affected by spinocerebellar ataxia 27 (SCA27), a rare autosomal dominant disease caused by mutations in fibroblast growth factor 14 ( FGF14 ). Despite normal structural neuroimaging, psychiatric manifestations and intellectual disability are part of the SCA27 phenotype raising the need for functional neuroimaging. Here, we used clinical assessments, structural and functional neuroimaging to characterize these new SCA27 patients. Since one patient presents with a psychotic disorder, an exploratory study of markers of schizophrenia associated with GABAergic neurotransmission was performed in fgf14 −/− mice, a preclinical model that replicates motor and learning deficits of SCA27. Methods: A comprehensive characterization that included clinical assessments, cognitive tests, structural neuroimaging studies, brain metabolism with 18 F‐fluorodeoxyglucose PET ([18F] FDG PET) and genetic analyses was performed. Brains of fgf14 −/− mice were studied with immunohistochemistry. Results: Nine patients had ataxia, and all affected patients harboured an interstitial deletion of chromosome 13q33.1 encompassing the entire FGF14 and integrin subunit beta like 1 ( ITGBL1 ) genes. New features for SCA27 were identified: congenital onset, psychosis, attention deficit hyperactivity disorder and widespread hypometabolism that affected the medial prefrontal cortex (mPFC) in all patients. Hypometabolism in the PFC was far more pronounced in a SCA27 patient with psychosis. Reduced expression of VGAT was found in the mPFC of fgf14 −/− mice. Conclusions: This is the second largest SCA27 family identified to date. We provide new clinical and preclinical evidence for a significant psychiatric component in SCA27, strengthening the hypothesis of FGF14 as an important modulator of psychiatric disease. Abstract :